James Ensor - wildest dreams beyond impressionism - Todts, Herwig 1958-; Becker, Astrid 1971-; Callen, Anthea; Canning, Susan M.; Carpiaux, Véronique; Clark, Timothy 1959-; Depelchin, Davy; Florizoone, Patrick; Gildman, Noémie; Gonnissen, Adriaan; Jonckheere, Evelien 1985-; Nagai, Yuri; et al. (KMSKA, 2024)
ames Ensor’s visionary spirit takes us on a journey through his manifold universe of still lifes, self-portraits, savage visions, carnival and satire. In the course of his career, Ensor grew into an unruly gamechanger who personally reset the rules of art. As he did so, he resolutely distanced himself from the classical European ideal of beauty and from the Impressionism that had initially fascinated him. Ensor did not limit himself to painting – he also unleashed his passion for experiment in detailed drawings, huge collages and potent etchings. His love for the fanciful resulted in characteristically grotesque representations of countless wild dreams. The pulse of a thrilling late nineteenth century beats through the more than two hundred works reproduced in this book. Ensor constantly surprises us with his contrasts between the comical and the macabre, the refined and the wanton, atmospheric bourgeois interiors and morbid skeletons. Drawing on their wide-ranging expertise, fifteen authors each highlight specific facets of the Ostend artist’s developing practice to paint a fresh and comprehensive picture of Ensor’s life and work. This publication accompanies the exhibition In Your Wildest Dreams – Ensor Beyond Impressionism from 28 September 2024 until 19 January 2025 at the Royal Museum of Fine Arts Antwerp (KMSKA)
Colophon: This publication accompanies the exhibition "In Your Wildest Dreams. Ensor Beyond Impressionism" from 28 September 2024 until 19 January 2025 at the Royal Museum of Fine Arts Antwerp (KMSKA)
Keywords: Ensor, James -- 1860-1949; Ausstellungskatalog -- Koninklijk Museum voor Schone Kunsten -- 28.09.2024-19.01.2025 -- Antwerpen; Aufsatzsammlung